Arginine‐Rich Peptide‐Based mRNA Nanocomplexes Efficiently Instigate Cytotoxic T Cell Immunity Dependent on the Amphipathic Organization of the Peptide. Issue 13 (24th April 2017) - Udhayakumar, Vimal K.; De Beuckelaer, Ans; McCaffrey, Joanne; McCrudden, Cian M.; Kirschman, Jonathan L.; Vanover, Daryll; Van Hoecke, Lien; Roose, Kenny; Deswarte, Kim; De Geest, Bruno G.; Lienenklaus, Stefan; Santangelo, Philip J.; et al.
Abstract : To date, the mRNA delivery field has been heavily dominated by lipid‐based systems. Reports on the use of nonlipid carriers for mRNA delivery in contrast are rare in the context of mRNA vaccination. This paper describes the potential of a cell‐penetrating peptide containing the amphipathic RALA motif to deliver antigen‐encoding mRNA to the immune system. RALA condenses mRNA into nanocomplexes that display acidic pH‐dependent membrane disruptive properties. RALA mRNA nanocomplexes enable mRNA escape from endosomes and thereby allow expression of mRNA inside the dendritic cell cytosol. Strikingly, RALA mRNA nanocomplexes containing pseudouridine and 5‐methylcytidine modified mRNA elicit potent cytolytic T cell responses against the antigenic mRNA cargo and show superior efficacy in doing so when compared to RALA mRNA nanocomplexes containing unmodified mRNA. RALA's unique sequence and structural organization are vital to act as mRNA vaccine vehicle, as arginine‐rich peptide variants that lack the RALA motif show reduced mRNA complexation, impaired cellular uptake and lose the ability to transfect dendritic cells in vitro and to evoke T cell immunity in vivo. Abstract : T‐cell immunity elicited by mRNA vaccines is heavily influenced by the delivery system. Cell penetrating peptide containing amphipathic RALA motifs condenses mRNA into nanocomplexes that efficiently translocate their mRNA cargo from endocytic vesicles to the cytosol. Through unique immune activation and enhanced expression, nucleoside modified mRNA complexed with RALA peptide induces potent antigen specific cytolytic T cells in vivo.